AB0459 Analysis of integrated radiographic data for two long-term, open-label extension studies of adalimumab. (23rd January 2014) - van der Heijde, D.; Landewé, R.; Keystone, E.C.; Breedveld, F.C.; Liu, S.; Mozaffarian, N.
Abstract : Background: Accurate analysis of radiographic progression in rheumatoid arthritis (RA) has been challenging because most evaluations use change in Sharp score either between only 2 time points or between multiple time points but only at 1 assessment, limiting the accuracy and statistical power of treatment comparisons. Objectives: To use a data integration approach to evaluate longitudinal radiographic data obtained from long-term trials of adalimumab (ADA) in RA patients (pts). Methods: Data are from 2 phase 3, randomized, placebo (PBO)-controlled trials of ADA: PREMIER was a 2-year (yr) trial conducted in MTX-naïve pts with early RA, 1 with an ongoing 8-yr open-label (OL) extension; DE019 was a 1-yr trial of pts with long-standing RA and an inadequate response to MTX, 2 with a completed 9-yr OL extension. This post hoc analysis evaluated available radiographic data from the original PBO+MTX and ADA 40 mg every other week+MTX arms through 8 and 10 yrs of treatment in PREMIER and DE019, respectively. Radiographic progression was assessed using the modified total Sharp score (mTSS) as change (Δ) from baseline (BL). Radiographs were assessed at Yrs 2, 3, 5, and 8 (PREMIER) and Yrs 1, 2, 3, 5, 6, 8, and 10 (DE019). At each assessment yr, radiographs from BL and select prior yrs were re-read. A mixed effect model was used to evaluate the repeated measurements at different time points and different assessments in the integrated data analysis. ΔmTSS at each post-BL time point was estimated by least square mean, and hence, annualized change was calculated. Results: Radiographic data from 452 (PREMIER: 215, PBO+MTX; 237, ADA+MTX) and 327 (DE019: 162, PBO+MTX; 165, ADA+MTX) pts with BL and at least 1 post-BL radiograph were available through up to 8 and 10 years of therapy, respectively. Pts completing up to 8 yrs of therapy in PREMIER experienced an estimate of ΔmTSS of 11.1 (PBO+MTX) and 3.9 (ADA+MTX) units; pts in DE019 experienced an estimate of ΔmTSS of 6.6 (PBO+MTX) and 0.9 (ADA+MTX) units through up to 10 yrs of treatment. Radiographic progression was most apparent in those pts receiving PBO+MTX during the randomized portions, but annual progression rates slowed dramatically upon switch to OL ADA±MTX therapy in both trials (Figure). Interestingly, pts initially treated with ADA+MTX maintained low levels of annual progression in both long-term studies, experiencing an estimated change of approximately 0.5 units or less throughout. Conclusions: A longitudinal, data integration analysis factoring in all available time points enabled a robust estimate of radiographic progression, and, in the present examples, confirmed and extended the radiographic superiority of initial combination therapy with ADA+MTX. Disclosure of Interest: D. van der Heijde Consultant for: Abbott, Amgen, AstraZeneca, BMS, Centocor, Chugai, Merck, Novartis, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, Wyeth, R. Landewé Grant/Research support from: Abbott, Amgen, Centocor, Pfizer/Wyeth, UCB, BMS, Consultant for: Abbott, Amgen, Centocor, Pfizer/Wyeth, UCB, BMS, Speakers Bureau: Abbott, Amgen, Centocor, Pfizer/Wyeth, UCB, BMS, E. Keystone Grant/Research support from: Abbott, AstraZeneca, Biotest, BMS, Centocor, Genentech, Merck, Nycomed, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, AstraZeneca, BMS, Centocor, Genzyme, Merck, Novartis, Pfizer, UCB, F. Breedveld Consultant for: Centocor, Schering-Plough, Amgen/Wyeth, Abbott, S. Liu Shareholder of: Abbott, Employee of: Abbott, N. Mozaffarian Shareholder of: Abbott, Employee of: Abbott